2009
DOI: 10.1089/end.2008.0586
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Infusion of Local Anesthetic Decreases Narcotic Use and Length of Hospitalization After Laparoscopic Renal Surgery

Abstract: A continuous infusion of 0.25% bupivacaine at 4 mL/hour through the ON-Q elastomeric infusion pump is a safe and effective adjunct in postoperative pain management after laparoscopy. Initial experience with the ON-Q Pain Relief System results in decreased narcotic use and decreased length of hospitalization compared with traditional postoperative pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Secondary ABG with iliac crest bone is standard in many comprehensive cleft care protocols (Paterson et al, 2016), despite the fact that donor site pain remains a significant limitation (Rawashdeh, 2008; Meara et al, 2011; Myeroff and Archdeacon, 2011). Attempts to more effectively manage donor site pain have often been met with disappointing results (Wilkes and Thomas, 1994; Hahn et al, 1996; Morrison and Jacobs, 2003; Blumenthal et al, 2005; Singh et al, 2005; Morgan et al, 2006; Baig et al, 2006; Singh et al, 2007; Charous, 2008; Coulthard et al, 2008; Elder et al, 2008; Ouaki et al, 2009; Yoost et al, 2009; Sbitany et al, 2010; Sbitany et al, 2010; Meara et al, 2011; Visoiu, 2014; Muzaffar et al, 2016). Furthermore, alternatives to autologous bone have been explored to alleviate donor site morbidity, such as allograft and Bone Morphogentic Protein-2 (BMP-2) (Francis et al, 2013; Sivak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary ABG with iliac crest bone is standard in many comprehensive cleft care protocols (Paterson et al, 2016), despite the fact that donor site pain remains a significant limitation (Rawashdeh, 2008; Meara et al, 2011; Myeroff and Archdeacon, 2011). Attempts to more effectively manage donor site pain have often been met with disappointing results (Wilkes and Thomas, 1994; Hahn et al, 1996; Morrison and Jacobs, 2003; Blumenthal et al, 2005; Singh et al, 2005; Morgan et al, 2006; Baig et al, 2006; Singh et al, 2007; Charous, 2008; Coulthard et al, 2008; Elder et al, 2008; Ouaki et al, 2009; Yoost et al, 2009; Sbitany et al, 2010; Sbitany et al, 2010; Meara et al, 2011; Visoiu, 2014; Muzaffar et al, 2016). Furthermore, alternatives to autologous bone have been explored to alleviate donor site morbidity, such as allograft and Bone Morphogentic Protein-2 (BMP-2) (Francis et al, 2013; Sivak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published on the use of the catheter-based ON-Q PainBuster postoperative pain management system, which provides a constant infusion of anesthetic(s) to a target anatomical site, spanning a variety of surgical procedures. [20][21][22] Published clinical evidence shows improved postoperative pain outcomes after surgical procedures (both open and laparoscopic), including cardiothoracic (thoracotomy 41 and sternotomy 42 ), ob-gyn (cesarean section 43 and hysterectomy 44 ), orthopedic (spine, 45 joint 20 ), bariatric, 46 urological, 47 plastic, 22 as well as abdominopelvic surgical procedures (eg, hernia). 48 The key benefits achieved over the more traditional opioidbased treatments were reduced pain scores, reduced opioid requirements (and thus reduced side effects), and shortened hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…(5, 14, 2123) A systematic review and meta-analysis of local anesthetic wound infusion catheters for colorectal surgery showed that their use was associated with significantly reduced opioid consumption. (22) In a prospective study of the use ON-Q local anesthetic infiltrating catheters for open nephrectomy, postoperative narcotic consumption was reduced, and patients had earlier return of bowel function and more rapid discharge from the hospital.…”
Section: Discussionmentioning
confidence: 99%